Importance of teachers’ competency through students’ perception in relationships between parental involvement and motivation with students’ achievement - Omar, Rosmaria; Ahmad, Nor Aniza; Hassan, Siti Aishah; Roslan, Samsilah (UTM Press, 2018)
Teachers’ competency is important for the process of student ‘well development’ in ensuring quality learning especially for students in vocational colleges. Teachers’ competency will give positive effects on students’ academic development and skills, and help teachers to improve their teaching techniques. Therefore, collaboration between vocational college management and parents shall be increased to achieve integrated quality education, efficient teachers and contributes to positive impacts on students’ standard achievement. Sample of 430 students were randomly stratified and the data had been collected by using questionnaire. The collected data had been analysed through Structural Equation Modeling (SEM) by using AMOS 22.0. Result of analysis showed that the hypothesized model had fulfilled the fitness indexes criteria where RMSEA = .062, CFI = .954, TLI = .936 and Chi square/ df = 2.404. Implication of this study is giving contribution on improvement of theoretical model for the relationship of teachers’ competency, parental involvement, achievement motivation and students’ achievement in the Malaysian education system.n sebagai satu usaha dalam meningkatkan penguasaan kemahiran membaca murid SJKC.